Koincydencja tożsamości jako model badania pogranicza polsko-niemieckiego = Coincidence of identity as the Polish-German borderline model study - Młyńczyk, Łukasz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The debate about identity in the process of its decryption should be placed in the logic of a network system. In the course of the evolution of international structures a multi-level governance model was developed. It is all the more important that from the subnational, through national (today wrongly regarded as the basic one) to transnational, there is an axis for a discourse around the issues which are called either international or European (i.e., community).
Keywords: pogranicze polsko-niemieckie; tożsamość